Toxicity beyond accumulation of Titanium after a short exposure period of Mytilus galloprovincialis to spiked seawater - Monteiro, Rui (2020)
Titanium is the ninth most abundant element in the Earth's crust, being present in rocks, soils, and sediments (Skrabal, 1995; Taylor and McLennan, 1985). Because this element is poorly soluble in water (Knauss et al., 2001; Schmidt and Vogelsberger, 2009), dissolved Ti is usually present at very low concentrations in riverine, estuarine and coastal waters, with concentrations between 0.01 and 5.5 μg L−1 (Skrabal, 2006; Yan et al., 1991; Yokoi et al., 1991). At present, TiO2 nanoparticles (nTiO2) are widely used in various manufacture materials, such as additives in pharmaceuticals and food colorants, toothpastes, solar cells, sunscreens, cosmetics and boat paints (Kaegi et al., 2008; Robichaud et al., 2009; Wahie et al., 2007; Wang et al., 2007). With an estimated production of 88,000 metric tons worldwide in 2012 (Keller and Lazareva, 2014), and a predicted increase of nTiO2 production, the discharge of Ti into aquatic systems will inevitably increase (Batley et al., 2013; Gondikas et al., 2014). Several studies have already revealed the impacts of nTiO2 in bivalve species, such as the scallop Chlamys farreri, the mussels Mytilus galloprovincialis and Mytilus edulis, the clam Ruditapes philippinarum, and the oyster Crassostrea virginica. Alterations on the immune system, oxidative status, and metabolism have been reported in previous studies (Barmo et al., 2013; Canesi et al., 2010; Della Torre et al., 2015; Doyle et al., 2015; Huang et al., 2016; Johnson et al., 2015; Marisa et al., 2015; Shi et al., 2017; Wang et al., 2014; Xia et al., 2017). Once in the aquatic environment nTiO2 may interact with the water components and enhance the availability of Ti to organisms (Fan et al., 2016; Pavagadhi et al., 2014; Romanello and de Cortalezzi, 2013; Tong et al., 2013; Xiong et al., 2011). Whether this enhanced availability contributes to change the past assumption that toxicity of Ti was negligible (Ophus et al., 1979; Roman et al., 1988) is, to the best of authors’ knowledge, not clarified. The present study aimed to understand the interaction of Ti with the mussel M. galloprovincialis, a commonly used bioindicator of contamination, exposed to seawater spiked with Ti(IV). Variations of Ti concentrations in seawater and mussels, and biochemical markers related to oxidative stress and metabolic capacity were examined after 96 h and 14 days of Ti addition to water.